Oxyfunctionalization of limonene using vanadium complex anchored on functionalized SBA-15 - Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2005)
VO(Salten) complexes, where Salten = 3-[N,N'-bis-3(salicylidenamino)ethyltriamine], have been covalently anchored on to functionalized SBA-15. The formation and integrity of the complex have been confirmed by elemental analysis, Fr-IR, X-ray diffraction (XRD) and BET measurements and the complex was used for the oxyfunctionalization of limonene in presence of urea hydroperoxide (UHP) as the oxidizing agent. The oxyfunctionalization of limonene resulted in limonene oxide, carvone, carvacrol and carveol. Anchored complex showed better catalytic activity than the neat complex, while the neat complexes has deactivated in the reaction due to formation of inactive alpha-oxo-bridged dimers, the covalently anchored complexes remained stable throughout the reaction. The anchored complex could be easily separated from the products and could be reused. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: covalently anchored vanadium complex; functionalized Si-SBA-15; limonene; oxofunctionalization; UHP